Online teaching: Education in times of crisis or education of the future? - Dabetić Valerija (Anali Pravnog Fakulteta u Beogradu)
The paper analyzes different aspects of online teaching as the prevalent method of education at the Belgrade University Faculty of Law during the COVID-19 pandemic. The starting assumption is that the combination of online and traditional teaching better meets the modern requirements of the labor market and better trains law students for different career paths and modern professions. Since digital technology has become an indispensable part of all spheres of law, we advocate the idea that an adapted form of online teaching develops young lawyers' digital literacy. The paper draws on the results of a qualitative study, i.e., four focus group discussions with teachers at the Faculty of Law who conducted classes during the pandemic. Despite different personal affinities and experiences regarding online classes, the general opinion was that online teaching should become part of the teaching practice, with noticeable disparity regarding its intensity and implementation.